Luminescence characteristics of quartz from Brazilian sediments and constraints for OSL dating - GUEDES,CARLOS C.F. (2013)
This study analyzes the optically stimulated luminescence (OSL) characteristics of quartz grains from fluvial, eolian and shallow marine sands of northeastern and southeastern Brazil, with especial focus on the applicability of the single-aliquot regenerative dose (SAR) dating protocol. All analyzed Brazilian sediments presented relatively high OSL sensitivity and good behavior regarding their luminescence characteristics relevant for radiation dose estimation. However, some samples from the Lençóis Maranhenses region in northeastern Brazil showed inadequate OSL sensitivity correction, hampering the implementation of the SAR protocol and their ability to behave as a natural dosimeter. While the shallow marine and eolian samples showed a narrow and reliable dose distribution, the fluvial sample had a wide dose distribution, suggesting incomplete bleaching and natural doses estimates dependent on age models.